Reflections on teaching ratio and proportion using Lesson Study - Christian Domondon; Mark Joseph Corpuz; Mark Carranza; Imriani Moroki; Ferdie Ching; Levi Elipane (Diversitas Journal, 2024)
Lesson Study provides an opportunity for teachers to engage in layers of individual and collaborative reflections in, on, and for practice to improve the teaching and learning process. This paper reports on reflections on teaching ratio and proportion online using Lesson Study, which could improve the teaching-learning process, specifically on pedagogy. The study consisted of three major stages: Lesson Planning, Lesson Study Proper, and Reflection through post-lesson discussion. The research lesson study proper was participated in by Grade 9 students in a school in the Philippines and six teachers—one taught the lesson, and the other five observed the class via Zoom. Also, the six teachers were participants in the post-lesson discussion. The data gathered from this descriptive qualitative study were analyzed using thematic analysis. It was concluded that in teaching ratio and proportion, the distinction between terminologies must be emphasized so there will be no confusion and for the students to use what is proper.